A green and sustainable strategy for leather manufacturing: Endow dehydrated hide with consistent and durable hydrophobicity. (10th January 2023) - Xu, Shuangfeng; Shi, Bi
Abstract: A green and sustainable approach for leather-making was explored by imparting dehydrated hide (DL) with durable hydrophobicity through reacting with silane coupling agent (TMS). The rational control of hydrolysis and condensation rates of TMS was the key point for achieving efficient penetration and full reaction of TMS in DL, so as to obtain hydrophobic leather (HL-TMS). It was found that the leather-like HL-TMS could be fabricated when the DL with 5% water content reacted with TMS for 12 h under 30 °C at pH 6.0. In these conditions, TMS was evenly distributed in HL-TMS and provided HL-TMS with excellent water resistance, owning a dynamic waterproof time up to 163 h. Moreover, HL-TMS displayed exceptional hydrophobic durability against pH, UV, friction and organic solvents. Compared with DL, the collagen fibers of HL-TMS were well dispersed, and the porosity of which was 59.6% higher than chrome-tanned leather. In addition, the shrinkage area of HL-TMS in heating was 5.03%, remarkably less than chrome-tanned leather (12.11%), while its physical strengths and softness (9.6 mm) were higher than those of chrome-tanned leather. The results suggested that hydrophobic modification could substitute conventional tanning for manufacturing leather, and this hydrophobic modification-based strategy might push leather-making into a cleaner process. Graphical abstract: Image 1 Highlights: A tanning-free leather-making approach based on hydrophobic modification of DL by TMS was explored. HL-TMS was successfully fabricated when DL with 5% water content reacted with TMS for 12 h at pH 6.0. HL-TMS behaved excellent water resistance with dynamic waterproof time up to 163 h. The area shrinkage rate of HL-TMS was 5.03% in heating, which was remarkably less than chrome-tanned leather (12.11%). HL-TMS displayed higher physical strengths and softness than chrome-tanned leather.